AB0998 Diagnostic value of 14-3-3 (ETA) in rheumatoid arthritis. (15th June 2017) - Novikov, A; Aleksandrova, E; Cherkasova, M; Popkova, T; Luchihina, E; Novikova, D; Karateev, D
Abstract : Background: Protein 14-3-3η (eta) involved in the upregulation of inflammatory and joint damage factors [1]. 14-3-3η is the candidate biomarker of rheumatoid arthritis (RA) [2]. Objectives: To evaluate the clinical utility of 14-3-3η for diagnosis of RA. Methods: We studied 44 patients (pts) with RA, 5 man and 39 women, median (25–75 percentile) of age 45 (33–59) years; disease duration is 10 (5–20) months, DAS28 5, 2 (4, 4–6, 2); 5 pts with systemic lupus erythematosus, 4 – ankylosing spondylitis, 5 – OVERLAP, 4 with psoriatic arthritis and 20 healthy individuals. 14-3-3η, anti-cyclic citrullinated peptide autoantibody (anti-CCP) was measured in serum by commercial enzyme-linked immunosorbent assays, IgM rheumatoid factor (IgM RF) measured – by immunonephelometry. Results: The diagnostic sensitivity of 14-3-3η for RA (cut off 0, 19 ng/ml) is 70, 5%, specificity – 83, 7%; positive likelihood ratio – 4, 33, negative likelihood ratio – 0, 35; positive predictive value – 81, 6%, negative predictive value – 73, 5%; AUC – 0, 78 (CI 0, 68–0, 88). Concomitant presence of 14-3-3η and IgM RF, anti-CCP was determined in 68%, 73% of the patients with RA respectively. 14-3-3η had correlation with IgM RF (r=0, 7, p<0, 05). Conclusions: Serum 14-3-3η are helpful for the diagnosis of RA. References: van Beers-Tas MH, Marotta A, Boers M, Maksymowych WP, van Schaardenburg D. A prospective cohort study of 14-3-3η in ACPA and/or RF-positive patients with arthralgia. Arthritis Res Ther. 2016 Apr 1;18:76. doi: 10.1186/s13075–016–0975–4. Maksymowych WP, Boire G, van Schaardenburg D, Wichuk S, Turk S, Boers M, Siminovitch KA, Bykerk V, Keystone E, Tak PP, van Kuijk AW, Landewé R, van der Heijde D, Murphy M, Marotta A. 14-3-3η Autoantibodies: Diagnostic Use in Early Rheumatoid Arthritis. J Rheumatol. 2015 Sep;42(9):1587–94. doi: 10.3899/jrheum.141385. Epub 2015 Jul 15. Disclosure of Interest: None declared